2015
DOI: 10.1182/blood-2015-02-626259
|View full text |Cite
|
Sign up to set email alerts
|

The LSD1 inhibitor RN-1 induces fetal hemoglobin synthesis and reduces disease pathology in sickle cell mice

Abstract: Key Points RN-1 treatment of SCD mice results in increased human fetal γ-globin induction and fetal hemoglobin synthesis. RN-1 treatment of SCD mice significantly reduces sickling, hemolysis, and tissue injury with no obvious adverse side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 53 publications
2
76
0
Order By: Relevance
“…The results confirm and extend our previous studies in the sickle cell mouse model showing that RN-1 increased F cells, F reticulocytes, and γ-globin mRNA to levels similar to decitabine, the most potent HbF-inducer known. 32,33 However, both these drugs elicit only small increases of γ-globin expression in the SCD mouse model compared to the magnitude observed in baboons, emphasizing the importance of using nonhuman primate, such as baboons, to test the effect of HbFinducing drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results confirm and extend our previous studies in the sickle cell mouse model showing that RN-1 increased F cells, F reticulocytes, and γ-globin mRNA to levels similar to decitabine, the most potent HbF-inducer known. 32,33 However, both these drugs elicit only small increases of γ-globin expression in the SCD mouse model compared to the magnitude observed in baboons, emphasizing the importance of using nonhuman primate, such as baboons, to test the effect of HbFinducing drugs.…”
Section: Discussionmentioning
confidence: 99%
“…31 Two recent studies have shown that RN-1, a more potent and specific LSD-1 inhibitor than TCP, induced γ-globin expression in human and baboon erythroid progenitors and a sickle cell mouse model. 32,33 In this study we have tested the effect of RN-1 in baboons and confirm that it is a highly potent in vivo inducer of HbF synthesis.…”
mentioning
confidence: 99%
“…In addition, the contribution of LSD1 in leukemogenesis has been demonstrated, and the use of LSD1 inhibitors is being investigated as a new therapeutic strategy (49,50). The roles of LSD1 in hematopoiesis are various, and include the differentiation switch between erythropoiesis and myelopoiesis (44), the terminal differentiation of some hematopoietic lineages (47,48), maintenance of the undifferentiated state of plasma cells (46), globin switching (51)(52)(53), and the self-renewal of hematopoietic stem cells (48). Here, we unveiled new roles of LSD1, as a down-regulator of the endothelial characteristics and promoter of the hematopoietic commitment in hemangioblasts.…”
Section: Discussionmentioning
confidence: 99%
“…35 Subsequent studies showed inhibition of erythroid maturation by tranylcypromine, which precludes further clinical development. However, another LDS1 inhibitor, RN-1, was recently shown to induce HbF in sickle cell mice with increased F-cells 36 and decreased numbers of sickle red cells in the peripheral blood, suggesting RN-1 may also reduce disease pathology.…”
Section: Modulation Of Epigenetic Marks To Activate Hbf Expressionmentioning
confidence: 99%